DEVELOPMENT OF BISCUITS FOR PREGNANT WOMEN ANEMIA USING MOCAF-GARUT SUPPLEMENTED BY MORINGA LEAVES AND CHICKEN LIVER - Adani Taqiyyah Nur Zaman (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2019)
Background: Iron deficiency anemia (IDA) is often suffered by pregnant women. Preventive action by giving iron tablet during pregnancy had been performed with unsatisfying result. Kelor leaves has micro nutrient substance that is needed by pregnant women. This study aims to develop additional food product such as mocaf (Modified cassava flour)-arrowroot biscuit that’s supplemented with kelor (Moringa Oleifera) leaves and chicken liver with high level iron and protein as well as sensory characteristics that can be accepted in pregnant women. Methodology: This study used Random Groups Design. There were two factors tested; they were, the proportion of mocaf : arrowroot (P), 80:20 (P1); 75:25 (P2); 70:30 (P3) and the comparison of kelor leaves : chicken liver (K), 50% addition to total flour, 25% : 25% (K1); 35% : 15% (K2). There were 6 treatment combinations repeated four times until 24 samples were obtained. Chemistry variable analysis used F-test (95%) and then continued with Duncan’s Multiple Range Test (DMRT) 5%, sensoric variable used Friedman Test and then continued with Double Compare Test 5%. The best treatment combination used Effectivity Index Test. Result: The best treatment combination was P3K1, in which biscuit had proportion of the composite of mocaf : arrowroot 70:30 and the comparison of kelor leaves : chicken liver 25%:25% with energy value 460.35 kkal/100g; water content 4.40% bb; gray value 1.76% bk; protein level 6.09% bk; fat content 17.71% bk; carbohidrat content by difference 74.43% bk and iron level 9.89 mg. Conclusion: Second trisemester pregnant women anemia could be given eleven biscuits and for third semester pregnant women anemia could be given sixteen biscuits in a day to fulfil the iron need. Key words: Iron Deficiency Anemia, Pregnant women, PMT biscuit, mocaf, Kelor leaves (Moringa Oleifera), Arrowroot flour, Chicken liver.